Perceptions of the Seriousness of Mispronunciations of English Speech Sounds - Moedjito ; ITO Harumi (TEFLIN, 2008)
The present study attempts to investigate Indonesian EFL teachers and native English speakers perceptions of mispronunciations of English sounds by Indonesian EFL learners. For this purpose, a paper-form questionnaire consisting of 32 target mispronunciations was distributed to Indonesian secondary school teachers of English and also to native English speakers. An analysis of the respondents perceptions has discovered that 14 out of the 32 target mispronunciations are pedagogically significant in pronunciation instruction. A further analysis of the reasons for these major mispronunciations has reconfirmed the prevalence of interference of learners native language in their English pronunciation as a major cause of mispronunciations. It has also revealed Indonesian EFL teachers tendency to overestimate the seriousness of their learners pronunciations. Based on these findings, the study makes suggestions for better English pronunciation teaching in Indonesia or other EFL countries.